STUDIES ON THE MECHANISM OF HORMONAL INDUCTION OF ALKALINE PHOSPHATASE IN HUMAN CELL CULTURES : I. Effects of Puromycin and Actinomycin D - Griffin, Martin J. (The Rockefeller University Press, 1966)
Increased alkaline phosphatase activity is induced in certain epithelial cell cultures by hormones with adrenal glucocorticoid activity or their analogues such as prednisolone (Δ(I)-hydrocortisone). Enzyme induction occurs in two distinct phases. During the first 12 hr after the addition of prednisolone, there is a small increase in alkaline phosphatase levels. After 15 to 24 hr, the enzyme activity shows a sudden, marked linear rise, reaching a maximum at 60 to 80 hr. Puromycin blocks enzyme induction immediately, even when added during the period of rapid increase of enzyme. Actinomycin D blocks induction when added no later than 8 hr after the addition of prednisolone. On the other hand, Actinomycin D added during the phase of rapid enzyme induction has no effect for at least 12 hr. These findings suggest that de novo protein synthesis is involved in prednisolone induction of alkaline phosphatase and that the RNA messenger for this enzyme is relatively stable.